On the relation between carbonyl stretching frequencies and the donor power of chelating diphosphines in nickel dicarbonyl complexes. Issue 13 (17th March 2017) - Fusè, Marco; Rimoldi, Isabella; Cesarotti, Edoardo; Rampino, Sergio; Barone, Vincenzo
Abstract : We unravel the mechanisms of chelation-bond formation in nickel dicarbonyl complexes with bidentate phosphines and demonstrate that σ donation drives the carbonyl stretching response to the metal–ligand bond formation. Abstract : The relation between spectroscopic observables and the detailed metal–ligand bonding features in chelation complexes is addressed using both experimental and state-of-the-art theoretical and computational methods. We synthesized and characterized a set of six nickel dicarbonyl complexes of general formula [Ni(CO)2 (PP)], where PP is an atropoisomeric chelating diphosphine ligand. The analysis of the obtained experimental data and the basicity and oxidative potentials of the free ligands suggests a close relation between the donor ability of the chelating ligand and the carbonyl stretching frequencies observed in the complexes. We then use theory to unravel the detailed mechanisms of chelation-bond formation in terms of partial charge flows between the molecular orbitals of the fragments. By extending the promising, recently published natural orbitals for chemical valence/charge displacement (NOCV/CD) analysis scheme we provide a thorough, quantitative description of the several charge fluxes following the metal–ligand bond formation and demonstrate that the carbonyl stretching frequencies in the considered complexes selectively respond to the σ-donation charge flow from the phosphorus lone pairs of the ligands, with the frequency shift being in quantitative correlation with the extent of the ligand-to-metal charge transfer.